Analisis Perbandingan Kinerja Framework Codeigniter Dengan Express.Js Pada Server RESTful Api - Luky Mulana; Kamal Prihandani; Adhi Rizal (Peneliti.net, 2022)
Application Programming Interface (API) is an interface that is able to integrate data and connect an application that runs on many platforms so that it can be connected to each other, one of the API implementations is the RESTful API. The choice of technology in making a RESTful API is very important because it can affect the performance of the server. The Codeigniter and Express.js frameworks are two backend technologies that are used to create RESTful APIs. To determine the performance of each framework, it is necessary to test using the performance testing method to determine the response time and CPU and memory usage. The results of the test show that Express,js has an average response time of 438,64 ms faster than the Codeigniter framework which obtains an average response time of 551,72 ms, while for CPU and memory usage, the Express.js framework consumes more than the Codeigniter framework. . So Express.js is suitable for systems that are accessed by many users and are placed on servers with high specifications. While the Codeigniter framework is suitable to be implemented for systems with fewer user access and can be placed on servers with low specifications.